2018
DOI: 10.15171/jcvtr.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive impairment after acute coronary syndrome: Prevalence and characterization in a hospital-based cardiac rehabilitation program sample

Abstract: Introduction: Prospective studies have shown the relation between acute coronary syndrome (ACS) and neurocognitive dysfunction with prevalence ranging between 10.51% and 66.8%. The present study aims to determine the prevalence level of neurocognitive dysfunction; the relations between sociodemographic, clinical and emotional variables and neurocognitive functioning in a sample of ACS patients. Methods: The sample comprised of 53 patients engaged in cardiac rehabilitation within 3 months after an ACS. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 30 publications
(39 reference statements)
1
20
2
Order By: Relevance
“…The total sample from the nine studies included 6457 ACS patients (Table 3), ranging from 53 16 to 2174 17 patients between studies. The age mean of patients ranged from 51 16 to 77 years. 14 The proportion of males ranged from 57% 18 to 100%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The total sample from the nine studies included 6457 ACS patients (Table 3), ranging from 53 16 to 2174 17 patients between studies. The age mean of patients ranged from 51 16 to 77 years. 14 The proportion of males ranged from 57% 18 to 100%.…”
Section: Resultsmentioning
confidence: 99%
“…14 Of the nine studies, six were undertaken in the USA 14,15,17,19–21 and one each in the UK, 22 Spain 18 and Portugal. 16 Study designs included longitudinal cohort studies ( n = 8) 14,1622 and a RCT ( n = 1). 15…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the prevalence of neurocognitive dysfunction was high in this patient group, although their sample size was small. 9 Bedside measurement of mental status in elderly patients post ACS within 48 h of admission demonstrated cognitive impairment in approximately one-third of patients. This was then found to be associated with an increased risk of mortality at one year and an increase in rehospitalisation at three months.…”
Section: Prevalence and Patterns Of Cognitive Impairment In Acute Cormentioning
confidence: 99%